Clinico-Pathological Correlation In Classification Of Leprosy - Mittal Rani Radha; Gupta Kamala; Gupta Seema (Wolters Kluwer Medknow Publications, 1997)
102 cases of leprosy were studied clinically and histopathologically according to Ridleyâ€s scale of 1977; 8 odd cases of leprosy where criteria were not exactly fulfilled were excluded. Clinico-histopathological correlation (CHC) was studied in 94/102 cases. CHC was seen in 75/94 (79.7%). 63/102 cases had hypopigmented macules with variable degree of anaesthesia and CHC was seen in 49/63 (77.7%)